Stem cell therapy for spinal cord injury A plea for rationality - Mathai, Khalil Isaac; Sasivadanan, MS; Sudumbraker, S; Sahoo, PK (Indian Journal of Neurotrauma, 2008)
The discovery of neural stem cells has offered a glimmer of hope to those afflicted by neurodegenerative diseases or those bearing the brunt of neurological insult. Spinal cord injuries affect young adult males predominantly and there is often pressure on the medical community to ‘do something’. The hype in the lay press on this modality has fostered in many, the hope that these cells can nurture neurological recovery. Presented below, is an overview of the current state of stem cell research and the impact of this and other newer modalities on the paradigms of spinal cord injury management.
Keywords: neural stem cells; spinal cord injury